MENINGKATKAN DIMENSI KREATIVITAS PROFIL LULUSAN MURID MELALUI MODIFIKASI PERMAINAN BOLA TANGAN BERBASIS PROBLEM BASED LEARNING DALAM PEMBELAJARAN PJOK DI SMPN 8 BANJARBARU - Rangga Saputra; Arie Rakhman; Trinaldi Andika Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
With adapted handball games at SMPN 8 Banjarbaru, this study attempted to improve the creative component of students' graduation profiles using a Problem Bssed Learning-based PJOK course. The two cycles of CAR that were used in the study consisted of planning, taking action, observing, and reflection. Data was collected through questionnaires, documentation, and observation. The study revealed that the graduate profile's creative component improved throughout each cycle. During the pre-cycle phase, the proportion of students' creative ideas that were deemed adequate was 60%. In Cycle I, the "good" category included 66% of the observation results and 67% of the questionnaire data. The questionnaire data showed an increase in the very good category to 82%, and the observation findings increased to 79% during Cycle II. Consequently, the graduate profile's creative dimension was successfully improved by PJOK learning, which emphasizes problem-based learning via modified handball games.